Structural analysis of strained LaVO3 thin films. (13th March 2015) - Rotella, H; Copie, O; Steciuk, G; Ouerdane, H; Boullay, P; Roussel, P; Morales, M; David, A; Pautrat, A; Mercey, B; Lutterotti, L; Chateigner, D; et al.
Abstract: While structure refinement is routinely achieved for simple bulk materials, the accurate structural determination still poses challenges for thin films due on the one hand to the small amount of material deposited on the thicker substrate and, on the other hand, to the intricate epitaxial relationships that substantially complicate standard x-ray diffraction analysis. Using both electron and x-ray diffraction, we analyze the crystal structure of epitaxial LaVO3 thin films grown on (1 0 0)-oriented SrTiO3 . Transmission electron microscopy study reveals that the thin films are epitaxially grown on SrTiO3 and points to the presence of 90° oriented domains. The mapping of the reciprocal space obtained by high resolution x-ray diffraction permits refinement of the lattice parameters. We finally deduce that strain accommodation imposes a monoclinic structure onto the LaVO3 film. The reciprocal space maps are numerically processed and the extracted data computed to refine the atomic positions, which are compared to those obtained using precession electron diffraction tomography.